Interest Rate Setting on the Swiss Franc Repo Market - Sébastien Kraenzlin (Swiss Journal of Economics and Statistics, 2009)
Repurchase agreements (repos) are secured money market transactions. The cash taker provides collateral in the form of securities and in return receives money from the cash provider. To ensure the continuous covering of the cash amount, the definition of eligible collateral, its handling and valuation play an important role. This is mainly because the collateral nearly eliminates credit risk. In Switzerland, Swiss franc repos are almost exclusively conducted via the highly standardized repo platform, with four different pre-defined collateral baskets. Each basket comprises different security categories, such as government bonds or covered bonds. This paper analyzes the interest rate setting on the repo market with data from June 1999 to June 2005. It evaluates, among others, if the securities provided as collateral influenced the repo rate or not. Surprisingly, a price differentiation with respect to the collateral provided is found. Consequently the paper provides an explanation for this finding and discusses a possible solution.
Keywords: C23; E43; E52; E58; 330; Repurchase Agreement; Repo; Monetary Policy; Panel Data Econometrics; Collateral; Switzerland